2013
DOI: 10.1371/journal.pgen.1003308
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Association of NUP98 with the Human Genome

Abstract: Faithful execution of developmental gene expression programs occurs at multiple levels and involves many different components such as transcription factors, histone-modification enzymes, and mRNA processing proteins. Recent evidence suggests that nucleoporins, well known components that control nucleo-cytoplasmic trafficking, have wide-ranging functions in developmental gene regulation that potentially extend beyond their role in nuclear transport. Whether the unexpected role of nuclear pore proteins in transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
159
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(172 citation statements)
references
References 56 publications
13
159
0
Order By: Relevance
“…Consistent with the hypothesis that Nup98 is a specific transcription activator, it also has been demonstrated that Nup98 interacts with histone-modifying enzymes CBP/p300 and histone deacetylases (45,46). Given that Nup98 regulates gene expression of developmental genes in mammals and Drosophila (19,20,35) and we observed regulation of antiviral genes in Drosophila, we suggest that Nup98 may have functions in regulating cell intrinsic antiviral gene expression in mammalian systems. Indeed, it has long been recognized that Nup98 is involved in antiviral defense (34,(47)(48)(49).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Consistent with the hypothesis that Nup98 is a specific transcription activator, it also has been demonstrated that Nup98 interacts with histone-modifying enzymes CBP/p300 and histone deacetylases (45,46). Given that Nup98 regulates gene expression of developmental genes in mammals and Drosophila (19,20,35) and we observed regulation of antiviral genes in Drosophila, we suggest that Nup98 may have functions in regulating cell intrinsic antiviral gene expression in mammalian systems. Indeed, it has long been recognized that Nup98 is involved in antiviral defense (34,(47)(48)(49).…”
Section: Discussionsupporting
confidence: 89%
“…Recent studies have revealed a direct role for Nup98 in gene expression, particularly in the transcriptional regulation of developmental and immune genes (19,20,22,35). Thus, we hypothesized that Nup98 may similarly regulate the expression of antiviral genes independent of its role in nucleo-cytoplasmic transport.…”
Section: Resultsmentioning
confidence: 96%
“…5C), suggesting that this truncated form also interferes with transport-independent activities of DRA2. These results support our hypothesis that the FGcontaining NtDRA2 fragment has a dominant-negative effect on the expression of DRA2-regulated genes, an activity also observed for the N-terminal mNup98 fragment (Liang et al, 2013). Since NtDRA2 does not localize in the NPC, it should interfere with pools of DRA2 that localize either in the nucleus or the cytoplasm.…”
Section: Dra2 Is a Dynamic Nupsupporting
confidence: 88%
“…The C-terminal region of mNup98 (CtNup98) mediates its interaction with the NPC (Hodel et al, 2002) and contains a minimal cleavage domain that is evolutionarily conserved also in the C-terminal part of Arabidopsis DRA2 and DRAL, which suggests that the C-terminal region of DRA2 mediates the interaction with the NPC in plants. Overexpression of mammalian NtNup98 fused to GFP results in a dominant-negative form that interferes with endogenous mNup98 activity (Liang et al, 2013). Overexpression of the N-terminal part of DRA2 (amino acids 1-779, NtDRA2) fused to GFP in Col-0 (35S:NtDRA2-GFP lines) caused stunted growth.…”
Section: Dra2 Encodes Arabidopsis Nup98amentioning
confidence: 99%
“…23 However, although the 2 proteins still associate with one another in the NPC, it is generally believed that cleavage into 2 different polypeptides allows the FG-Nup domain of this protein to be dynamic and have a role in gene regulation, while the a-solenoid portion remains a stable structural member of the outer ring complex. 24,25 The tripeptide catalytic residues in the trypanosome ortholog (TbNup158) have altered during evolution to prevent cleavage, resulting in the protein being incorporated into the TbNPC outer ring as a single protein, possibly to eliminate this dynamism and negate a role in gene regulation which is unusual in trypanosomes (see below and Fig. 2).…”
Section: Copy and Paste: The Npc's Scaffold Arose Through Ancient Dupmentioning
confidence: 99%